Make your own Thunderbirds Models - "Fitsimmons, Jim" (Hodder & Stoughton: London, 1993)
A collection of models to make and play with, based on the Thunderbirds TV series. Step-by-step instructions show children how to make their own Thunderbirds models at home. Transform everyday materials into replicas of Thunderbirds 1, 2, 3, 4, 5 and the Mole, and create a model of Tracy Island.
Keywords: Models and modelmaking